MICROBIAL BIOCONVERSION TO PRODUCE NUTRACEUTICAL AND PHARMACEUTICAL BIOACTIVE COMPOUNDS - Siti Mahyuni (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
he bioconversions of bioactive health supporting compounds using certain microorganisms have long been known, however it has not been widely applied in industrial scale to produce nutraceutical and products of high economic value. This review article will discuss the group of steroids, carotenoids and statins which were produced by microbial bioconversion using the various substrates and conditions. The information presented in this article were collected from scientific books and articles in national and international journals which can be validated and traced back to their sources through many sites such as google.com, google scholar, NCBI and Science Direct. From the information compiled in this article, it can be concluded that the bioconversion of bioactive compounds by microorganisms has shown positive results and potential to be further optimized and applied in an industrial scale to produce natural bioactive compounds as basic ingredients for nutraceutical and pharmaceutical products with high economic value.